Aspekte des Menschseins im Alten Mesopotamien : eine Studie zu Person und Identitat im 2. und 1. Jt. volume Chr. - Steinert, Ulrike. (Cuneiform Monographs, 2012)
Being the first monographic study of this kind in the field of Assyriology, this book comprises an investigation of Ancient Mesopotamian concepts of the human person. Concentrating on Akkadian cuneiform texts from the 2nd and 1st millennium BC, the author examines the characteristics and attributes attached to human beings and the notions of the person as a composite being through a semantic analysis of Akkadian terms for the body, body parts and aspects of the self, which can be termed \'souls\'. Through an examination of a wide range of textual sources and an interdisciplinary approach, this study shows that the Mesopotamian views of personhood share amazing similarities with those of the neighbouring ancient cultures, but often differ from our own. "...in short, as a piece of modern Assyriological scholarship it is very well done and a tribute to its author's capabilities and accomplishments." Benjamin R. Foster, Yale University